Tourism Investment and Land Use Change in the Northern Piedmont of the Western High Atlas (1989-2022) - Hamza Ait Zamzami; Mohammed Elaanzouli; Ayoub Zahrani; Jamila Saidi; Taieb Boumeaza; Muhammad Musiyam (Forum Geografi)
This study aimed to investigate the profound influence of tourism investment on the Northern Piedmont of the western High Atlas over 34 years in response to the escalating global trend of tourism-driven land-use changes, particularly in the Marrakesh region. In this context, the driving forces behind the significant transformation of agricultural land and bare soils into tourism-driven investments were evaluated as well as the critical role of accessibility in shaping spatial shifts. The method used high-resolution (10 m) satellite images from Spot 1 (1989), Spot 5 (2003 & 2010), and Sentinel 2 (2022) through remote sensing methods to investigate the historical land-use changes over 34 years. The results showed significant transformations in land-use based on the correlation between improved transportation infrastructure and the growth of tourism ventures, underscoring the role of roads and facilities as catalysts. The analysis suggested the need for reflection on the consequences of unregulated tourism growth, aiming to balance economic benefits with environmental and socio-cultural challenges in sensitive regions. Although tourism significantly contributed to economic development and employment opportunities, it also posed risks when not managed prudently. This underscored the need to strike a harmonious equilibrium between economic prosperity as well as preserving the unique natural beauty and cultural heritage of the region. The insights provided in this analysis had broader implications for responsible planning and management of tourism development in sensitive ecological and cultural regions. In conclusion, a thoughtful and sustainable approach was needed to safeguard the delicate balance between economic prosperity and environmental preservation.